Child sexual abuse awareness among parents visiting pediatric outpatient hospital services in Southern India - Tabassum Parvin; Padmavathi Nagarajan; Shivanand Kattimani; Venkatesh Chandrasekaran; Rajeev Seth (Telangana Journal of Psychiatry, 2025)
Background: Child sexual abuse can have a deleterious impact and is of growing concern globally. Its prevention requires better awareness among the public from different cultures. Objectives: The objective of this study was to measure the awareness level of parents using the Child Sexual Abuse Awareness Scale. Participants and Setting: The current survey was conducted among parents visiting a pediatric outpatient service at a large tertiary care hospital in southern India. Methods: We used a semi-structured data sheet to collect sociodemographic data and used the Child Sexual Abuse Awareness Scale to measure the awareness levels of parents (CSAASP) (Berkmen and Seçim, 2019). It is a reliable and validated 23-item scale with three factors (myths, teachings and action against abuse, and recognizing signs of abuse). We analyzed the association between the level of awareness regarding child sexual abuse among parents attending the outpatient department and their sociodemographic variables. Results: The mean age of the participants was 31.8 years (range: 19–52 years). Out of the 273 participants, we had equal representation from both genders. Sixty-three percent were from rural residential backgrounds. Scores on CSA awareness significantly associated with participants’ level of education (Kruskal–Wallis test and Chi-square [df] = 9.139 [3], P = 0.027) and location of residence (Mann–Whitney U-test, Z = −3.081, P = 0.002). We found a significant correlation between the level of CSA awareness and the age and monthly household income of the participants (ρ = 0.124, P = 0.041; ρ = 0.214, P = 0.000). Conclusions: Survey participants (parents) had a better awareness of CSA. The level of CSA awareness among parents was significantly better in those with higher education and those hailing from urban residential locations.